Implementation of Indonesian Traditional Law System E-Encyclopedia (ENSHI) in Civics Learning Towards Increasing Student's National Insights - Agung Nugraha Putra; Susan Fitriasari; Dede Iswandi (Department of Civic Education, 2022)
This research is motivated by the problem of the lack of national insight possessed by the younger generation, especially junior high school students. In order to overcome this problem, a movement for inculcating the values of Indonesian nationalism in Civics learning is needed by applying a digital encyclopedia based on local wisdom called the e-Encyclopedia of the Indonesian Customary Law System (ENSHI). ENSHI is an innovative and applicable digital learning media, that summarizes all studies, theories, and arguments of Indonesian customary law which are comprehensively poured into the form of a website. The study used a quantitative approach and a quasi-experimental study method involving seventh-grade students of SMPN 1 Cimahi. The study involved two research samples, namely class VII A as the experimental class and class VII D as the control class. The data collection technique used is a series of pre-test and post-test with data analysis techniques using statistics with the help of IBM SPSS Version 25 software. The results obtained from this study are PPKn learning outcomes in the experimental class that apply ENSHI learning media showing significant results compared to the control class which only applies conventional learning.